Beyond monotherapy: multimodal strategies integrating immune checkpoint inhibitors in lymphoma management - Li, Yuxiao; Zheng, Ruixin; Pan, Bing; Wang, Xiaobo; Zhang, Lina; Gao, Haiying; Li, Li (Frontiers in Immunology, 2025)
The advent of immune checkpoint inhibitors (ICIs) has revolutionized lymphoma therapy, though efficacy varies markedly between Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL). ICIs targeting the programmed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) pathway show significant efficacy in HL, but limited benefit in NHL subtypes including diffuse large B-cell lymphoma; in T-cell lymphomas and natural killer (NK) cell lymphomas, PD-1 inhibitors demonstrate significant efficacy in extranodal NK/T-cell lymphoma, but response rates remain limited for most peripheral T-cell lymphoma subtypes. The PD-1/PD-L1 axis is central to lymphoma immunotherapy: PD-1/PD-L1 blockade counters tumor immune evasion, whereas CTLA-4 inhibition enhances early T-cell activation in lymphoid tissues. Additional checkpoints also contribute to disease progression by mediating T-cell exhaustion, underscoring their therapeutic relevance. This review delineates the mechanistic rationale and clinical implications of combining ICIs with conventional therapies (chemotherapy, radiotherapy), targeted agents, and emerging modalities. Synergistic combinations have shown promise in overcoming resistance and amplifying antitumor immunity. Clinical trials highlight PD-1 inhibitor-chemotherapy/radiotherapy regimens improving response and survival rates in select lymphomas. Immuno-combination therapies achieve superior efficacy in specific subtypes despite heightened immune-related adverse events. By synthesizing evidence across different combination approaches, this perspective provides clinicians with an integrative framework that transcends traditional disease subtype boundaries, offering broader insights for therapeutic decision-making in lymphoma immunotherapy. Current challenges include developing predictive biomarkers and optimizing management of immune-related adverse events. Collectively, integrating ICIs with complementary modalities offers transformative potential, yet requires rigorous mechanistic exploration and clinical validation to maximize therapeutic index and durability of responses.